Optimalisasi Manajemen Peternakan pada Peternakan Kelompok Tani Ternak Cengkir Gading di Desa Sawahan, Kecamatan Ngemplak, Boyolali - Tampubolon, Bahroin Idris; Makky, Muhammad Rafif Mahasin; Aditya, Muhamad Aflah; Akbar, Muhammad Shafy; Fauziah, Tazkia Nurul; Alida, Yumiko; Priditya, Nazwa; Imana, Sirin; Puspita, Salma Dara (Jurnal Pusat Inovasi Masyarakat, 2025)
Livestock Farmers Group (LFG) Cengkir Gading is one of the farmer groups that utilizes the potential of livestock in Sawahan Village. Their livestock activities are quite good, but farmers discuss several problems in several aspects of livestock management. The livestock management optimization program at LFG Cengkir Gading aims to make farmers increasingly understand effective livestock management and optimize livestock results. The method of implementing innovation is carried out through observation, interviews, socialization, focus group discussions, coercion, training, monitoring and evaluation. The IPB Innovation KKN-T Team implemented a livestock management optimization program in all aspects of livestock. Aspects that are considered include cages, animals, feed, and animal health. The optimization of livestock management at LFG Cengkir Gading carried out by the KKN-T Team received a positive response from LFG Cengkir Gading farmers. Farmers become more aware of the optimal livestock management system. Farmers feel very helped by the program that is implemented. In addition, farmers can feel the results of the program with improvements in aspects of animals, cages, feed, and animal health.